Evaluation of Artificial Intelligence–Blockchain Technology Integration in the Industry 4.0 Era: Systematic Literature Review - Sidabukke, Aripin; Wijaya, Jonsen; Br. Tarigan , Agata Theodora Febriani; Pratama, Vandika; Lotandes, Aldo; Joosten Joosten (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the integration of Artificial Intelligence (AI) and Blockchain technology to optimize processes within the Industry 4.0 framework. The background of this research is the increasing demand for operational transparency, data security, and autonomous decision-making in modern manufacturing and supply chains. While Industry 4.0 generates massive data (Big Data), it faces challenges in data integrity and intelligent automation. The research method used is a Systematic Literature Review (SLR) with a qualitative approach, analyzing academic publications from 2020 to 2025. Data were collected from databases such as IEEE Xplore, Scopus, and ScienceDirect, focusing on integration architecture and use cases. The results show that AI integration (specifically machine learning) on the Blockchain enables decentralized predictive maintenance, autonomous smart contracts, and secure data provenance for AI training. The synergy between AI's analytical power and Blockchain's immutability shows significant potential to increase efficiency, reduce fraud, and build trust among stakeholders. This indicates that the AI-Powered Blockchain model has a positive and significant effect on optimizing Industry 4.0 systems. Thus, this integration can be recommended as an innovative framework for building autonomous, transparent, and intelligent industrial systems.